163k views
16 votes
For the function find f-1(x)

For the function find f-1(x)-example-1
User Megaoctane
by
6.0k points

2 Answers

7 votes

since you know that to get the inverse of any expression we start off by doing a quick switcheroo on the variables and then solve for "y".


\stackrel{f(x)}{y}=\sqrt[3]{\cfrac{x+6}{2}}\implies \stackrel{\textit{quick switcheroo}}{x=\sqrt[3]{\cfrac{y+6}{2}}}\implies \stackrel{\textit{cubing both sides}}{x^3=\cfrac{y+6}{2}} \\\\\\ 2x^3=y+6\implies 2x^3-6=\stackrel{f^(-1)(x)}{y}

User Kmaork
by
5.2k points
12 votes
The answer is C. i know because i looked it up
User TheTreeMan
by
5.0k points